GREEN ECONOMY AND SUSTAINABILITY: A LITERATURE ANALYSIS OF GLOBAL POLICIES - Loso Judijanto; Nekky Rahmiyati (CV. Adiba Aisha Amira, 2024)
This article analyses the literature focusing on global policies related to green economy and sustainability. The aim of this study is to identify the progress that has been made as well as the challenges faced in the implementation of the green economy in different countries. The study found that the success of a green economy depends on synergies between the government, private sector, and society, as well as a clear regulatory framework, adequate financial support, and technological innovation. In addition, public education and awareness-raising are important factors to support changes in consumer behaviour. In conclusion, a green economy has great potential to address global environmental challenges and achieve sustainable development goals, but requires a real commitment from all stakeholders to work together to create equitable and inclusive solutions.